Tolosa-Hunt syndrome following recurrent facial palsies - Shahrizaila, N.; Ramli, N.; Tan, C.T. (2010)
Tolosa-Hunt syndrome is typically associated with an inflammatory lesion in the cavernous sinus or orbital fissure, often requiring steroids for symptom resolution. In this report, we describe a case of Tolosa-Hunt syndrome preceded by several years' history of idiopathic recurrent facial palsies. The spontaneous resolution of THS in our case as well as prior facial nerve involvement supports the hypothesis that Tolosa-Hunt syndrome is part of a spectrum of idiopathic recurrent cranial neuropathy.